3D printing disruptions and strategic choice - a way forward. (2016) - Brophey, Glenn
Suppliers in the nascent 3D printing industry enjoy exciting potential as new applications are developing rapidly. On the other hand, increasing numbers of new entrants to this industry require incumbent firms to make product/market segment selection decisions to maintain competitiveness. Developing competitive advantage within segments is challenging given the mismatch between the time required to build the elements to deliver competitive offerings and the fast pace of disruptive events in the industry. This paper offers a way to make segment selections for the medium term by utilising a combination of well-accepted methods for decision-making (e.g. innovation diffusion forecasting, portfolio analysis, score carding, etc.). Examples of the diffusion rates analysis are provided for three segments. This is followed by a discussion of the merits of this normative approach to strategic decision-making compared to the merits of simply reacting to industry events.